1983
DOI: 10.1139/v83-160
|View full text |Cite
|
Sign up to set email alerts
|

Decay dynamics of aromatic thione triplet states in fluid solution

Abstract: This paper is dedicated to Pro/e.ssor Harry E. Gunrling on the occasiorl a/ his 65th birthdayA. SAFARZADEH-AMIRI, R. E. VERRALL, and R. P. STEER. Can. J . Chem. 61. 894 (1983). Phosphorescence emission and excitation spectra, quantum yields, and lifetimes of several aromatic thiones have been measured in fluid solution at room temperature. Excitation to any of the excited electronic states accessible in the near-uv and visible regions of the spectrum results in population of the lowest triplet state with near … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1984
1984
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Olefin precursors 1 − 3 were prepared according to literature methods. Olefin 4 was synthesized via Peterson olefination of 10,10-dimethylanthrone with fluorene. Olefin 5 was prepared from reaction of 2,3,6,7-dibenzocycloheptane-1-thione with diazofluorene, after the method of Schönberg et al Dications were formed via oxidation with a 30-fold excess of SbF 5 in SO 2 ClF at −78 or −90 °C …”
Section: Resultsmentioning
confidence: 99%
“…Olefin precursors 1 − 3 were prepared according to literature methods. Olefin 4 was synthesized via Peterson olefination of 10,10-dimethylanthrone with fluorene. Olefin 5 was prepared from reaction of 2,3,6,7-dibenzocycloheptane-1-thione with diazofluorene, after the method of Schönberg et al Dications were formed via oxidation with a 30-fold excess of SbF 5 in SO 2 ClF at −78 or −90 °C …”
Section: Resultsmentioning
confidence: 99%
“…[55][56][57][58][59] Two of these compounds, dithiosuccinimide ͑Fig. Large phosphorescence quantum yields ͑ P ͒ have been observed for several thioketones.…”
Section: B Test Casesmentioning
confidence: 99%
“…3,4 Unusually large phosphorescence quantum yields have been observed for several thioketones. 5,6 Ruth and the coworkers 7 confirmed that the T 1 ←S 0 absorption spectrum of 4H-pyran-4-thione (PT) was measured in static cell at room temperature (550-620 nm) in a seeded cold supersontic jet (580-600 nm) using the cavity ring-down (CRD) method. Theoretically, Marian et al 8 suggested that phosphorescence and non-radiative decay via intersystem crossing to the S 0 state were concurrent processes occurring at approximately equal rates of the order of 10 4 s -1 with the DFT/MRCI and SOMF methods.…”
Section: Introductionmentioning
confidence: 94%